Apple Maggot, Apple Maggot Fly, Rhagoletis pomonella (Walsh) (Insecta: Diptera: Tephritidae) - Howard V. Weems; Thomas R. Fasulo (EDIS, 2012)
The apple maggot, Rhagoletis pomonella (Walsh), also known as the apple maggot fly and “railroad worm,” is native to North America. Originally, it fed on the fruit of wild hawthorn (Crataegus spp.), but then became a primary pest of cultivated apples, especially in the northeastern United States and southeastern Canada. Summer- and early fall-maturing varieties are particularly vulnerable, but hard winter apples are sometimes infested. Thin skinned sweet and subacid varieties are most susceptible, but acid varieties may be attacked. This revised 4-page fact sheet was written by H. V. Weems, Jr. and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, March 2012.